PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP: KINERJA KEUANGAN PADA PT. LEBAH LESTARI PRIMA - Tira, Natalia Tia; Sidharta, Juaniva; Simanjuntak, Ramot P. (Universitas Kristen Indonesia, 2017)
The purpose of this study to determine the effect on the total quality management of the company’s financial performance in PT. LEBAHLESTARI PRIMA. Samples used in this study is 50 samples. Data used in this study are primary data in the form of a questionnaire and the company’s financial reporting period 2011 – 2015. Impact analysis using multiple linear regression analysis. Analysis shows together their total quality management effect on the financial performance of the company, it is shown from the results of the data processed by a number of significant results of testing the hypothesis of the four variabels that influence total quality management is a significant focus on the customer and the value obtained training with a focus on customer training of 0,003 and 0,000. And that no effect is continuous improvement and employee empowerment with the values obtained by continuous improvement and employee empowerment 0,091 at 0,488. Company size used in this study is the return on assets (ROA), return on equity (ROE) and net profit margin (NPM).Keyword: Total quality management, financial performance, financial ratio.